2022
DOI: 10.1186/s13059-022-02721-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid divergence of a gamete recognition gene promoted macroevolution of Eutheria

Abstract: Background Speciation genes contribute disproportionately to species divergence, but few examples exist, especially in vertebrates. Here we test whether Zan, which encodes the sperm acrosomal protein zonadhesin that mediates species-specific adhesion to the egg’s zona pellucida, is a speciation gene in placental mammals. Results Genomic ontogeny reveals that Zan arose by repurposing of a stem vertebrate gene that was lost in multiple lineages but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 161 publications
(323 reference statements)
2
19
0
Order By: Relevance
“…In contrast, a comparable word search retrieved annotated Atp4a, Haus5, and Gapdhs from 373, 376, and 294 placental genomes, respectively. Pairwise interrogation of the Atp4a-Haus5 intergenic region with the pig SMA20 cDNA sequence correctly identified the two-exon Pmis2 gene in five representative species (Figure 6), including the previously un-annotated pig locus, as well as Pmis2 from armadillo (Dasypus novemcitus), a relatively primitive species from superorder Xenarthra that diverged from the other species near the base of the placental phylogeny [28,29]. To determine if Pmis2 is conserved in Placentalia, we interrogated, via a pairwise comparison to the armadillo Pmis2 cds, the Atp4a-Haus5 intergenic sequences in the genomes of 20 randomly chosen placental species in which Pmis2 had previously evaded annotation, and we identified the two-exon Pmis2 gene in all 20 species.…”
Section: Identification Of Sma20 Orthologs and Genomic Locimentioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, a comparable word search retrieved annotated Atp4a, Haus5, and Gapdhs from 373, 376, and 294 placental genomes, respectively. Pairwise interrogation of the Atp4a-Haus5 intergenic region with the pig SMA20 cDNA sequence correctly identified the two-exon Pmis2 gene in five representative species (Figure 6), including the previously un-annotated pig locus, as well as Pmis2 from armadillo (Dasypus novemcitus), a relatively primitive species from superorder Xenarthra that diverged from the other species near the base of the placental phylogeny [28,29]. To determine if Pmis2 is conserved in Placentalia, we interrogated, via a pairwise comparison to the armadillo Pmis2 cds, the Atp4a-Haus5 intergenic sequences in the genomes of 20 randomly chosen placental species in which Pmis2 had previously evaded annotation, and we identified the two-exon Pmis2 gene in all 20 species.…”
Section: Identification Of Sma20 Orthologs and Genomic Locimentioning
confidence: 89%
“…Species variation in fertilization events necessarily require corresponding species differences in the nature or timing of molecular processes that mediate them. Rapid molecular evolution is a common feature of reproductive proteins in general [53] and of fertilization proteins in particular [29,52], with the adaptive divergence of any one protein potentially driving co-evolutionary divergence of its interacting partners [54]. Known sources of species variation in gene products include protein domain and wholegene duplications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][53][54][55], rapid sequence divergence by positive selection [29,53,54], concerted evolution by gene conversion [53][54][55], and individual variation in pre-mRNA splicing [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the divergence of a "speciation gene" may accurately represent species phylogeny because its evolution does not simply serve as a clock, but instead reflects the gene's direct contribution to speciation [58][59][60]. We previously found that Zan is a speciation gene in placental mammals, and its divergence tracks the evolutionary history of Eutheria [61]. Zan encodes the sperm protein zonadhesin, which mediates species-specific recognition of the egg, and rapid Zan evolution by intense positive selection promotes prezygotic reproductive isolation [62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Zan encodes the sperm protein zonadhesin, which mediates species-specific recognition of the egg, and rapid Zan evolution by intense positive selection promotes prezygotic reproductive isolation [62][63][64][65][66]. Despite being a single character evolving under positive selection, the Zan tree was generally congruent to a eutherian supertree [28,61] but did exhibit significant incongruencies in part, and presumably, because it was more highly resolved [61].…”
Section: Introductionmentioning
confidence: 99%